Negative-pressure dressings in lower limb skin grafts: a randomised control trial of PICO versus standard dressings - Lisa Ellis; Patricia Terrill; Warren Matthew Rozen (Australasian Journal of Plastic Surgery, 2021)
**Objective**: Negative-pressure wound therapy (NPWT) can reduce the incidence of exudate and haematoma beneath a split-thickness skin graft (SSG) compared with traditional standard dressings. However, NPWT has not been universally adopted for lower limb SSGs despite evidence that its use is linked with improved graft take and a tendency towards early mobilisation. PICO, an ultra-lightweight NPWT device now available in Australia, can provide a smaller, more manageable NPWT dressing. The primary objective of this study was to compare lower limb graft take rate in PICO versus standard dressing groups, and a secondary objective was comparing quality of life (QOL) in these groups.